Students’ Mathematical Problem-Solving Ability Reviewed from the Self-Confidence of Junior High School Students - Hermaitriyana; Samsir (Journal of Research on Mathematics Instruction (JRMI), 2021)
This study aims to describe the problem-solving abilities of students reviewed from their self-confidence. This method of this study is a qualitative descriptive research method. This study was conducted at Junior High School in Kampar. The subjects of this study were students of seventh grade in the 2020/2021 academic year as many as 20 students. The data analysis was carried out in three stages: data reduction, data presentation, and concluding. The data from this study were obtained by providing 5 items of mathematical problem-solving ability, distributing a questionnaire about self-confidence using a Likert scale in the form of a checklist, and conducting interviews. The results showed that there was a relationship between students' self-confidence and mathematical problem-solving abilities. From the questionnaire score category and the results of the problem-solving ability test given, it can be seen that 25% of students who have high self-confidence have good problem-solving skills because they meet all problem-solving indicators. Sixty percent of students who have moderate self-confidence have fairly good problem-solving abilities because they only meet part of the 4 problem-solving indicators. Fifteen percent of students belonging to the low category of self-confidence have problem-solving skills that are not good enough. The findings of this study can motivate teachers to raise students' self-confidence because students who have good self-confidence have good problem-solving abilities as well. The study's findings suggest that teachers should use methods and techniques to boost students' self-confidence in mathematics learning.